Comparison of peripapillary choroidal thickness between healthy subjects and patients with Parkinson's disease. - Elena Garcia-Martin; Luis E Pablo; Maria P Bambo; Raquel Alarcia; Vicente Polo; Jose M Larrosa; Elisa Vilades; Beatriz Cameo; Elvira Orduna; Teresa Ramirez; Maria Satue (PLoS ONE)
Purpose To study peripapillary choroidal thickness (PPCT) in healthy subjects using swept-source optical coherence tomography (SS-OCT), and to evaluate PPCT differences between Parkinson´s disease (PD) patients, and age- and sex-matched healthy controls. Design Case-control study. Methods 80 healthy subjects and 40 PD patients were consecutively recruited in this single institution study. The healthy subjects were divided into two populations: a teaching population (n = 40, used to establish choroidal zones) and a validating population (n = 40, used to compare measurements with PD patients). An optic disc 6.0×6.0 mm three-dimensional scan was obtained using Deep Range Imaging (DRI) OCT Triton. A 26×26 cube-grid centered on the optic disc was generated to automatically measure choroidal thickness. Five concentric choroidal zones were established and used to compare PPCT between healthy and PD patients. Results PPCT was significantly thicker in PD patients compared with controls in all four concentric zones evaluated (p≤0.0001). PPCT followed a similar pattern in controls and PD; it was thicker in the temporosuperior region, followed by the superior, temporal, nasal, and inferior regions. Conclusion PD patients presented with an increased PPCT in all zones surrounding the optic disc compared with healthy subjects. The peripapillary choroidal tissue showed a concentric pattern, with the thickness increasing with increasing distance from the optic nerve. SS-OCT could be useful for evaluating choroidal thinning in clinical practice.